The Effect of Velvet Antler Proteins on Cardiac Microvascular Endothelial Cells Challenged with Ischemia-Hypoxia - Xiao, Xiang; Xu, Shuqiang; Li, Lin; Mao, Min; Wang, Jinping; Li, Yanjun; Wang, Ziwei; Ye, Fei; Huang, Li (Frontiers in Pharmacology, 2017)
Velvet antler (VA) is a precious traditional Chinese medicine that is capable of repeated regeneration. Based on the Chinese medicine theory of coordination the heart and kidneys, VA has been employed to treat heart diseases, including ischemic heart disease, heart failure, and arrhythmia. We examined the effects of VA proteins on primary cardiac microvascular endothelial cells (CMECs) that were subjected to ischemia-hypoxia (IH) to investigate their effects on and mechanism of action in the treatment of ischemic heart disease. Velvet antler proteins (VA-pro) were extracted with water as the solvent, the ultrasonic wave method, and freeze-drying technology; then it was analyzed by Nano LC-MS/MS. In addition, the role of VA-pro in cell viability, proliferation, apoptosis, and mitochondrial membrane potential (MMP) were evaluated by the CCK8 assay, the EdU assay, the Annexin V-FITC/PI double-staining assay, and the JC-1 assay, respectively. Cell migration were evaluated by the scratch assay and the Transwell assay. The expression of apoptosis-associate proteins, Akt and p-Akt, and tube formation in Matrigel of CMECs were also detected. In total, 386 VA-pro were identified. Our results showed that IH significantly reduced the viability of the CMECs and suppressed copies of DNA to hold back CMEC proliferation, and it decreased the migration of CMECs, tubule formation ability, and MMP. VA-pro treatment resulted in an improvement in CMECs’ viability, proliferation, migration, and tubule formation ability as well as retaining the stability of MMP. Severe apoptosis was induced after CMECs were cultured in IH conditions, while VA-pro decreased the number of apoptotic cells. Similarly, the expression of pro-apoptosis proteins was higher, but the expression of anti-apoptosis proteins was lower in the IH group; VA-pro reversed these changes. These findings suggest that VA-pro ameliorate CMEC injuries induced by IH via regulating the PI3K/Akt signaling pathway.